Offshore wind : a comprehensive guide to successful offshore wind farm installation. - Thomsen, Kurt E. (Elsevier, 2012)
Offshore wind is the new blue horizon for Alternative Energy. One small offshore wind farm can produce more power than a whole coal plant, or a nuclear reactor. However, very few people have real experience getting an offshore wind farm up and running. This book is the first-ever roadmap to successful offshore wind installation. It provides a ready reference for wind project managers, teaching them how to deal with complications on-site, as well as for financers, who can utilize the text as an easy guide to asking the pivotal questions of petitioning wind project developers, whose planning stages will be improved by the book's expert advice on how to avoid wasting money by scoping out and mitigating potential problems up-front. Wind turbine manufacturers will benefit from insights into design optimization to support cheaper installation and hauling, thereby incurring lower project costs, and helping developers establish a quicker route to profitability. The book sheds light not just on HOW to solve a particul installation difficulty, but delves into WHY the problem may best be solved in that way. Readers will learn not just how to build successful offshore wind farms, but how to do so in the most safe and economical way possible. Enables all stakeholders to achieve cheaper, faster and safer offshore wind project realization Explains the different approaches to executing on- and offshore projects, highlighting the economic impacts of the various financial and operational choices Provides practical, proven advice on how tough challenges can be overcome, using real-life examples from the author's experiences to illustrate key issues.